A reference introduction to Jacques Rancière in a German edition (KULT_online, 2015)
With Jacques Rancière. Eine Einführung Oliver Davis provides a monograph that deals with all major texts by the French philosopher and which has now been republished in a German edition. The book starts with a discussion of Rancière and Louis Althusser and ends with a supplement briefly outlining those texts that had not previously appeared in the English reference edition. The volume draws focus on the book The ignorant Schoolmaster, because the thoughts developed in the book leading to a theory of radical equality are a very central and an important basis for Rancière's work.